Euro Area Policies : Staff Report for the 2014 Article IV Consultation With Member Countries. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the euro area recovery is taking hold. Real output has expanded for four consecutive quarters, and financial market sentiment has improved markedly. Complementary policy actions have supported demand, boosted investor confidence, and eased financial conditions. At the national level, governments have made further progress repairing sovereign and bank balance sheets and implementing structure reforms to restore competitiveness. At the area-wide level, the ECB has taken a wider range of measures to support demand and address fragmentation. Over the medium term, there is a risk of stagnation, which could result from persistently depressed domestic demand owing to deleveraging, insufficient policy action, and stalled structural reforms.